1994
DOI: 10.1111/j.1365-2958.1994.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel lectin‐like protein CHB1 is encoded by a chitin‐inducible Streptomyces olivaceoviridis gene and binds specifically to crystalline α‐chitin of fungi and other organisms

Abstract: The chb1 gene, which encodes the unique lectin-like alpha-chitin-binding protein CHB1 of Streptomyces olivaceoviridis, was cloned. Transformants of Streptomyces lividans harbouring the plasmid pCHB10 overproduced the extracellular CHB1 protein; the protein showed neither enzymatic nor antifungal activity. Biochemical analyses and immunofluorescence microscopy indicated that CHB1 binds strongly to alpha-chitin, but neither to chitosan and beta-chitin, nor to various types of cellulose. Within hyphae of fungi, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
134
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 44 publications
3
134
0
1
Order By: Relevance
“…The gene encoding this 53 kDa chitinbinding protein has not yet been identified. These data are consistent with those found for Streptomyces olivaceoviridis, in which a 20 kDa extracellular chitinbinding protein (CHB1) lacking chitinolytic activity has been identified (Schnellmann et al, 1994). It was suggested that the function of CHBl is to assist chitinase enzymes in hydrolytic digestion of bound chitin.…”
Section: Chitin-binding Domainssupporting
confidence: 81%
“…The gene encoding this 53 kDa chitinbinding protein has not yet been identified. These data are consistent with those found for Streptomyces olivaceoviridis, in which a 20 kDa extracellular chitinbinding protein (CHB1) lacking chitinolytic activity has been identified (Schnellmann et al, 1994). It was suggested that the function of CHBl is to assist chitinase enzymes in hydrolytic digestion of bound chitin.…”
Section: Chitin-binding Domainssupporting
confidence: 81%
“…While chitinases such as ChiA, ChiB, and ChiC also contain auxiliary CBMs, most microorganisms containing chitinase genes also contain a gene encoding for a homologue of CBP21, that is, a non-catalytic chitin-binding protein. Although these proteins have been hypothesized to assist chitinases in chitin degradation, possibly by disrupting chitin (25), this has so far not been shown experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are homologues of CBP21 (e.g. CHB1 from Streptomyces olivaoceviridis, which is 46% identical in sequence) that bind strictly to ␣-chitin (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations